Pengaruh Penerapan Model Scramble Oleh Guru Pak Terhadap Minat Belajar Siswa Kelas IX SMP Negeri 4 Tarutung Kecamatan Tarutung Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 (International Forum of Researchers and Lecturers, 2023)
The aim of this research is to determine the positive influence of the implementation of the Scramble Model learning by PAK teachers on the learning interest of class IX students at SMP Negeri 4 Tarutung, North Tapanuli Regency for the 2023/2024 academic year. The research method used is a quantitative research method with a descriptive inferential statistical approach. The population is all 103 class IX students of SMP Negeri 4 Tarutung, North Tapanuli Regency for the 2023/2024 academic year who are Protestant Christians and a sample of 28 people was determined using the cluster random sampling technique. Data was collected using a positive closed questionnaire with 41 items, namely 20 items for variable North Tapanuli 2023/2024 academic year: 1) Test analysis requirements: a) positive relationship test obtained rxy = 0.618 > rtable(a=0.05,n=28) = 0.374. b) Testing a significant relationship obtained tcount= 4.013 > ttable(a=0.05, dk=n-2=26)= 2.056. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂=